PESSOA COM DEFICIÊNCIA INTELECTUAL: A NOVA “RALÉ” DAS ORGANIZAÇÕES DO TRABALHO - Sérgio Sampaio Bezerra; Marcelo Milano Falcão Vieira (RAE: Revista de Administração de Empresas, 2012)
As social issues became part of current organizational studies, this essay analyses the promotion of equal opportunities to mentally challenged workers in the context of modern organizations, taking rationality as a guiding principle of their practices. The analysis is based on the affirmative action provided by the law, which obliges companies with more than 100 employees to hire people with disabilities, according to the definition of mentally challenged people and to the management practices that promote equal opportunities. This study applies the qualitative methodology and the theory of rationality. Results show that the management Practices of these workers have the instrumental rationality as basis. The conclusion is that this group does not have access to the same job opportunities and that human resources practices should change in order to promote equality.